2007
DOI: 10.1109/joe.2007.897071
|View full text |Cite
|
Sign up to set email alerts
|

Forward Scattering Observation With Partially Coherent Spatial Processing of Vertical Array Signals in Shallow Water

Abstract: In this paper, we address the problem of detecting an inhomogeneity in shallow water by observing changes in the acoustic field as the inhomogeneity passes between an acoustic source and vertical line array of receivers. A signal processing scheme is developed to detect the perturbed field in the presence of the much stronger primary source signal, and to estimate such parameters as the time when the inhomogeneity crosses the source-receiver path, its velocity, and its size. The effectiveness of incoherent, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Although relatively simple, this model has been useful for constructing algorithms for matched signal processing [4], and is the basis for the development of more refined models. Analytical calculations using the scattering matrix for a shallow sea, numerical simulations [2,3], and work by Kuz'kin et al as summarized in [9], have confirmed the validity of the proposed approach.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although relatively simple, this model has been useful for constructing algorithms for matched signal processing [4], and is the basis for the development of more refined models. Analytical calculations using the scattering matrix for a shallow sea, numerical simulations [2,3], and work by Kuz'kin et al as summarized in [9], have confirmed the validity of the proposed approach.…”
Section: Introductionmentioning
confidence: 71%
“…This processing yielded the best performance for detection and parameter estimation. Parameters include the length and cross-section area of inhomogeneity, its velocity and range, and the intersection instant [6][7][8][9]. Coherent spatial-temporal processing for horizontal receiving arrays and the methods of observation of a scattered signal outside of a main lobe of the diagram of scattering, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward scattering from an intrusive object could cause aberration in the waveguide response, providing an advantage in quietobject detection [5][6][7][8]. Transient aberration results from interference between the incident and scattered fields from an object [9], and its features can be actually difficult to be predicted in a multipath environment.…”
mentioning
confidence: 99%
“…Over the past few years, a detection method using forward scattering techniques was proposed for moving underwater targets, and a successful lake experiment was conducted with a foam plastic target [5,6]. A detection and localization algorithm based on the same techniques was described and evaluated based upon the experiment in a harbor environment [7].…”
mentioning
confidence: 99%